Psychological Distress Due to Political Demonstrations in Indonesian Democracy - Meysella Al Firdha Hanim; Zakaria Efendi; Febi Setiyawati (Prodi Sosiologi FISIP Universitas Teuku Umar, 2025)
Political demonstrations in recent years have become a significant phenomenon in Indonesia, as they not only reflect political instability but also generate mass psychological distress, which is rarely recognized as part of a social emergency. Previous studies tend to focus on structural issues such as the crisis of state legitimacy, elite polarization, or weak democratic institutions, but do not see demonstrations as triggering collective trauma, erosion of public trust, and emotional distress. To fill that void, this study examines how political demonstrations lead to psychological emergencies through social trauma, distrust of the state, and emotional distress due to media and economic conditions. To answer this, a qualitative content analysis of 15 national and regional online news reports from 1-31 August 2025 was used with thematic coding techniques. The research found three main things namely collective trauma emerged through violence by the authorities, casualties, and loss of security, a crisis of trust in state institutions seen in policy rejection, moral criticism, and demands for the dissolution of the DPR, and increased psychological distress due to media exposure, layoffs, and economic pressure. The contribution of this research lies in the repositioning of demonstrations as generators of collective psychological distress, not just political expression. This study recommends that the state adopt a more empathetic approach by implementing supportive policies, psychosocial safeguards, and non-traumatic avenues for participatory.